What's in a name - was John Curtin "Vigilant"? Analysing style to determine authorship. - Wallace, Lesley; Antonia, A.; Craig, H. (Monash University ePress, 2009)
Curtin researcher Tom Fitzgerald amassed a wealth of evidence that John Curtin wrote under the pen name "Vigilant" in the early years of his editorship of the Westralian Worker. If true, the personal and literary columns penned by "Vigilant" provide new insights into the inner temperament of Australia's war time Prime Minister. Fitzgerald's evidence for Curtin as "Vigilant" is presented in this paper and the attribution is further explored by applying stylistic tests developed at the Centre for Literary and Linguistic Computing at the University of Newcastle (NSW).